Poison center consultation reduces hospital length of stay. (3rd July 2022) - Farkas, Andrew; Kostic, Mark; Huang, Chiang-Chin; Gummin, David
Abstract: Context: Prior studies have observed shorter lengths of stay when practitioners consult a US poison control center (PCC) regarding hospitalized toxicology patients, but the most recent study used data from 2010. Since then, the implementation of the Affordable Care Act, a trend toward shorter hospitalizations and substantial adjustments in hospital charges have occurred. Methods: This is a retrospective study of administrative hospital data and poison center data obtained from the Wisconsin Hospital Association and Wisconsin Poison Center for patients treated from 2010 to 2017. Stratified analysis was used to investigate the potential effects of PCC consultation on hospitalization. Univariate and multivariable regression analysis was used to characterize which factors were associated with an increased rate of PCC consultation. Discussion: 127, 224 hospitalized cases were found, of which 44, 628 were entered into a stratified hospital charge and length of stay analysis. PCC consultation was associated with an 11.6 h (95% CI 10.4–13.0 h) shorter mean length of stay overall, with children aged 0–6 having a larger reduction of 1.18 days. While total charges were higher by 600 in PCC consultation cases in the overall analysis (95% CI 390–777), mean charges in patients aged 0–6 were 6695 lower when the PCC was consulted. PCC consultation was more likely to occur in cases involving children and adolescents, intentional overdoses (versus accidental or unknown intent), and women. Conclusions: Our findings suggest that PCC consultation should be encouraged to potentially shorten hospitalizations of poisoned patients, and for pediatric patients in particular. Intentionality and demographic factors affect the rate of PCC consultation for overdose, but the nature of these relationships is unclear.